Implementasi Program Padat Karya Dalam Mengurangi Pengangguran Di Kelurahan Balaroa Kecamatan Palu Barat - Ginatri Gina; Samsinas Samsinas; Hasriani Hasriani; Murniati Ruslan (Jurusan Pengembangan Masyarakat Islam Fakultas Dakwah dan Komunikasi Islam, UIN Datokarama Palu., 2025)
Work-intensive program is a program implemented by the government that involves the community aimed at empowering people who are not yet able to empower themselves. This study aims to determine the implementation and effectiveness of the labor-intensive program in reducing unemployment in Balaroa Village, West Palu District. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation, as well as data analysis through reduction, presentation, and verification. This study discusses the implementation of the labor-intensive program in Balaroa Village, West Palu District. The results of the study indicate that the labor-intensive program has a positive impact, including: helping people find jobs and income, improving family welfare, creating a clean environment that supports Palu City in achieving the Adipura award, and providing business opportunities for participants. However, this program also faces obstacles such as late salary payments, a decreasing number of participants without new recruitment, and a lack of discipline among some participants. Overall, the labor-intensive program has proven to be beneficial in reducing unemployment, supporting economic independence, and improving the standard of living of the community, especially vulnerable groups such as the elderly and single mothers.